2015
DOI: 10.1371/journal.pone.0134061
|View full text |Cite
|
Sign up to set email alerts
|

School-Age Children Are a Reservoir of Malaria Infection in Malawi

Abstract: Malaria surveillance and interventions in endemic countries often target young children at highest risk of malaria morbidity and mortality. We aimed to determine whether school-age children and adults not captured in surveillance serve as a reservoir for malaria infection and may contribute to malaria transmission. Cross-sectional surveys were conducted in one rainy and one dry season in southern Malawi. Demographic and health information was collected for all household members. Blood samples were obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
219
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(259 citation statements)
references
References 21 publications
28
219
2
2
Order By: Relevance
“…Specifically, submicroscopic malaria has been associated with older age, presumably due to partial immunity. 6,15,16 Although high levels of bed net usage during the study period suggested that bed nets may be partly responsible for this finding, bed net usage was not a risk factor for subpatent infection in our models, a finding consistent with prior reports. 16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, submicroscopic malaria has been associated with older age, presumably due to partial immunity. 6,15,16 Although high levels of bed net usage during the study period suggested that bed nets may be partly responsible for this finding, bed net usage was not a risk factor for subpatent infection in our models, a finding consistent with prior reports. 16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity.…”
supporting
confidence: 90%
“…6,15,16 Although high levels of bed net usage during the study period suggested that bed nets may be partly responsible for this finding, bed net usage was not a risk factor for subpatent infection in our models, a finding consistent with prior reports. 16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity. 11,17 Because PCR testing was only performed in the final year of the study, we could not assess changes in subpatent malaria over time.…”
supporting
confidence: 90%
“…[1][2][3] It can also be anticipated that current successes in lowering transmission may, through delaying the acquisition of immunity, lead to an increase in the incidence of clinical malaria in school-aged children in previously highly endemic areas in the future. 4 5 Malaria among school children has received increasing research attention over the last 10 years, with an expanding body of knowledge on the negative impacts that asymptomatic infection can have on health and education, as well as the deleterious effects of clinical attacks in this group.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of children in control and intervention schools at baseline: November 2010 (classes[1][2][3][4][5][6] …”
mentioning
confidence: 99%
“…In general, higher prevalence rates have been observed in West and Central Africa than in East Africa, but a great deal of heterogeneity has been observed with rates ranging from less than 5 percent to greater than 50 percent in different surveys. Recent studies in Malawi have emphasized the burden of malaria in school-age children and the role that those children play in acting as a reservoir of infection Walldorf and others 2015).…”
Section: Prevalence Of Malaria Parasitemia In School-age Childrenmentioning
confidence: 99%